1970
DOI: 10.3329/bjas.v37i1.9863
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Genotype, Age And Season On Hatchability Of Egg

Abstract: The study was conducted to study the effects of genotype and age of hen and hatching season on hatchability of egg. Hatching eggs were collected from hens having three genotypes viz. White Leghorn (WLH), Rhode Island Red (RIR) and Fayoumi covering three age groups (28 to 40, 41 to 60 and 61 weeks & above) at winter, monsoon and summer seasons. The study revealed that the highest (P<0.05) average hatchability was observed in winter (78.62%) followed by monsoon (76.70%) and summer (75.79%). Among differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…But in the age after 58 week, the fertility and hatchability was decreased. Similar result from Islam et al, (2008 ) highest (P<0.05)hatchability was found in the age group between 31 to 60 weeks (77.99%) followed by 61weeks (75.49%).The same result also observed by the Pramunik (2009) andTuncer et al (2006).…”
Section: Effect Of Ai On Different Production Parameterssupporting
confidence: 84%
“…But in the age after 58 week, the fertility and hatchability was decreased. Similar result from Islam et al, (2008 ) highest (P<0.05)hatchability was found in the age group between 31 to 60 weeks (77.99%) followed by 61weeks (75.49%).The same result also observed by the Pramunik (2009) andTuncer et al (2006).…”
Section: Effect Of Ai On Different Production Parameterssupporting
confidence: 84%
“…The highest fertility rate among the age of hen groups was found in middle aged hens followed by youngest group of hens and the fertility decreased with the increase in hen's age (Othman et al, 2014). Islam et al, (2008) showed that, with groups of breeder hens, the highest hatchability was found in 41 to 60 weeks and lowest in 28 to 40 weeks. There may be a distinct explanation for the higher fertility and hatchability % of eggs from peak production flocks.…”
Section: Disscutionmentioning
confidence: 89%
“…The nonappearance of a significant season effect on most of the traits under consideration may probably be due to that the broiler breeder flocks are reared under partially automated close confinement housing system. The best value of hatchability percentage was observed in winter (78.6) followed by monsoon (76.7) and summer (75.8) (Islam et al, 2008). Jesuyon and Salako (2013) showed that late wet season was most favorable for hatching activities in both Bovan Nera and ISA Brown parent stock compared with the remainder seasons.…”
Section: Disscutionmentioning
confidence: 94%
“…Usually, young birds show less broodiness character. Chicken at age of 41-47 weeks may be suitable for selecting broody hens [10] as the medium aged (40-61 weeks) hens give high hatching percentage compared to early and old aged birds [11]. c) Season of broodiness: The incubation season is also important as both the farmers and broody hens prefer to incubate eggs at a particular period of the year.…”
Section: Factors Affecting Broodinessmentioning
confidence: 99%